2020
DOI: 10.1016/j.celrep.2020.107588
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Establishing Pure Lung Cancer Organoids Limit Their Utility for Personalized Medicine

Abstract: Highlights d Frequent overgrowth of lung cancer organoids by normal airway organoids d Copy number profiling and IHC can be used to distinguish tumor and normal organoids d Low establishment rate of pure lung cancer organoids limits their clinical utility

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
145
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(168 citation statements)
references
References 32 publications
6
145
1
Order By: Relevance
“…35,36 Recently, Dijkstra et al established over 70 lung cancer organoids but only 17% of them were pure tumor organoids, and most of the organoids presented features of normal airway organoids. 19 Interestingly, our study showed that tumor cell purity of the PDOs had a high concordance with those in the original tissues, indicating that the accuracy of sampling could be critical for the success of organoid establishment. Moreover, we analyzed the association between tumor cell purity of the PDOs and corresponding VAFs and confirmed a significant linear relationship between tumor cell purity and VAF.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…35,36 Recently, Dijkstra et al established over 70 lung cancer organoids but only 17% of them were pure tumor organoids, and most of the organoids presented features of normal airway organoids. 19 Interestingly, our study showed that tumor cell purity of the PDOs had a high concordance with those in the original tissues, indicating that the accuracy of sampling could be critical for the success of organoid establishment. Moreover, we analyzed the association between tumor cell purity of the PDOs and corresponding VAFs and confirmed a significant linear relationship between tumor cell purity and VAF.…”
Section: Discussionmentioning
confidence: 70%
“…However, it is impossible to distinguish between tumor organoids and normal airway organoids based on histomorphological features only. 19 Therefore, we performed IHC staining to analyze the molecular characteristics of PDOs. IHC features of PDOs derived from ADCs and SCCs were highly concordant with those of their primary tumors.…”
Section: Establishment Of Pdo Models For Nsclcmentioning
confidence: 99%
“…Our current culture success rate is 16% (or 10% if only considering organoids confidently classified as NEC), which is too low for clinical implementation at the level of individual patients. This establishment rate is lower than for CRC biopsies (71%) (34) but in the same range as for non-small lung cell cancer (35,36) or advanced prostate cancer (37). Higher success rates may be achieved by optimizing the culture medium formulation, which may differ depending on the tissue of origin.…”
Section: Discussionmentioning
confidence: 90%
“…17,35,36 While the success rates of establishing cultures from pleural effusion are reportedly higher, 4, 13 their use is limited as only around a tenth of all of NSCLC patients present with malignant pleural effusions. 37 Other preclinical models such as tumor organoids or xenografts also have suboptimal success rates of 20-70% or 30-40%, respectively, 11,15,16,38,39 but these have an additional issue of long establishment times of one to three months for organoids or two to ten months for xenografts. 4,11,15,16,38 Prolonged ex vivo propagation in artificial conditions may cause a functional drift of cancer cells from their original identity, and also the patient's tumor may evolve during this time, further compromising the compatibility of preclinical cultures with the diagnostic clinical decision-making process.…”
Section: Discussionmentioning
confidence: 99%